Feasibility of the lidocaine injection method during esophageal endoscopic submucosal dissection. Issue 2 (6th September 2019) - Yoshizaki, Tetsuya; Obata, Daisuke; Ueda, Chise; Katayama, Norio; Aoki, Yasuhiro; Okamoto, Norihiro; Hashimura, Hiroki; Matsumoto, Masanori; Takagi, Megumi; Ikeoka, Seitaro; Yoshida, Ryutaro; Momose, Kenji; et al.
Abstract : Background and Aim: Esophageal endoscopic submucosal dissection (ESD) is often technically difficult due to intraoperative body movements. The level of sedation can be increased to suppress body movements, but this may not be successful in all cases. Using local analgesics for submucosal injection during ESD may aid in conscious sedation. This study evaluated the feasibility of the lidocaine injection method (LIM) during esophageal ESD. Methods: Twenty‐nine patients with superficial esophageal cancer were enrolled in this study at Osaka Saiseikai Nakatsu Hospital, and 1% lidocaine + 0.4% hyaluronate sodium was injected into the submucosa underneath the lesion during esophageal ESD. The main outcome was body movements that disturbed the procedure. Results: Most patients were male (90%), with a median age of 70 years (interquartile range [IQR]: 66–75 years old), and the median lesion size was 17 mm (IQR: 12–21 mm). The median injection volume of lidocaine was 70 mg (IQR: 55–79 mg). All lesions were successfully removed en bloc. In all cases, there were no body movements that disturbed the procedure. Regarding adverse events of sedation, five patients (17%) had hypotension, four patients (14%) had bradycardia, and seven patients (24%) had hypoxemia during ESD. Convulsions or arrhythmia as adverse events associated with lidocaine were not observed. Conclusions: Esophageal ESD with LIM did not cause body movements that disturbed the procedure. LIM may help create a stable conscious sedation method for esophageal ESD. Abstract : Esophageal endoscopic submucosal dissection (ESD) is often technically difficult due to intraoperative body movements. Esophageal ESD using the lidocaine injection method (LIM) did not cause body movements that disturbed the procedure in our study. LIM may help create a stable conscious sedation method for esophageal ESD.